Origin of the retention loss in ferroelectric Hf0.5Zr0.5O2-based memory devices. (1st February 2021) - Chouprik, Anastasia; Kondratyuk, Ekaterina; Mikheev, Vitalii; Matveyev, Yury; Spiridonov, Maxim; Chernikova, Anna; Kozodaev, Maxim G.; Markeev, Andrey M.; Zenkevich, Andrei; Negrov, Dmitrii
Abstract: For the decade, ferroelectric hafnium oxide films are attracting the interest as a promising functional material for nonvolatile ferroelectric random access memory due to full scalability and complementary metal-oxide-semiconductor integratability. Despite the significant progress in key performance parameters, particularly, the readout charge and voltage as well as the endurance, the developed devices can only be implemented by the electronics industry if they exhibit a standard retention time of 10 years. Material engineering modifies not only target ferroelectric properties, but also the retention time. To understand how to maintain the sufficient retention, the physical mechanism behind it should be clarified. For this purpose, we have fabricated the capacitor memory cell with a high rate of retention loss. Comparing the device performance with the results of capacitance transient spectroscopy, operando hard X-ray photoelectron spectroscopy and in situ piezoresponse force microscopy, we have concluded that the retention loss is caused by the accumulation of the positively charged oxygen vacancies at the interfaces with capacitor electrodes. The redistribution of charges during long-term storage of information is fully defined by the domain structure in memory cell. Graphical Abstract: Image, graphical abstract